2019
DOI: 10.1016/j.stemcr.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Activated Platelets Increase Adult Hippocampal Precursor Proliferation and Promote Neuronal Differentiation

Abstract: Summary Physical activity is a strong positive physiological modulator of adult neurogenesis in the hippocampal dentate gyrus. Although the underlying regulatory mechanisms are still unknown, systemic processes must be involved. Here we show that platelets are activated after acute periods of running, and that activated platelets promote neurogenesis, an effect that is likely mediated by platelet factor 4. Ex vivo , the beneficial effects of activated platelets and platelet fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 56 publications
4
86
0
Order By: Relevance
“…Additionally, platelets contain up to 95% of the circulating form of the amyloid precursor protein (Zhao et al, 2016), they express several neuronal receptors and inflammatory-signalling molecules (Wojsiat et al, 2017), and also contain α-synuclein (Michell et al, 2005). Recently, it has also been shown that platelets play an active role during adult neurogenesis in the hippocampus (Seidemann et al, 2019). Finally, changes in activation, aggregation and morphology of platelets have been reported in PD, DLB, amyotrophic lateral sclerosis and multiple sclerosis (Behari and Shrivastava, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, platelets contain up to 95% of the circulating form of the amyloid precursor protein (Zhao et al, 2016), they express several neuronal receptors and inflammatory-signalling molecules (Wojsiat et al, 2017), and also contain α-synuclein (Michell et al, 2005). Recently, it has also been shown that platelets play an active role during adult neurogenesis in the hippocampus (Seidemann et al, 2019). Finally, changes in activation, aggregation and morphology of platelets have been reported in PD, DLB, amyotrophic lateral sclerosis and multiple sclerosis (Behari and Shrivastava, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Changes of peripheral modulators in the blood upon exercise may directly influence NPCs associated with blood vessels and allow crosstalk with each other . Various circulating growth factors are involving in such a crosstalk, such as peripheral vascular endothelial growth factor, platelet factor 4, serotonin and IGF‐1 . Furthermore, recent studies highlighted an essential role of muscle in exercise‐induced cognitive benefits .…”
Section: Discussionmentioning
confidence: 99%
“…Platelets might not only have detrimental functions in the brain but also beneficial ones. For example, it has recently been demonstrated that the exercise-induced stimulatory effects on adult hippocampal neurogenesis are partially mediated through platelets (Leiter et al, 2019). In the context of stroke and of demyelinating lesions, platelet-derived factors promote neurogenesis and neuroprotection (Hayon et al, 2013;Au et al, 2014;Kazanis et al, 2015).…”
Section: Figure 5 | Continuedmentioning
confidence: 99%